Eksplorasi Kepribadian dan Perilaku Profesional Pendidik di Pondok Pesantren As-Sulthon Mersam Batang Hari : Perspektif Psikologi Industri - Raudatul Janna; Ahmad Arrifa’i; Yudi Agung Franata; Jamrizal Jamrizal; Samsu Samsu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
As a result of the analysis carried out, it can be concluded that the personality and professional behavior of educators at the As-Sulthon Mersam – Batang Hari Islamic Boarding School have a significant influence on the effectiveness of education at the Islamic boarding school. Warrior Personality Influences Professional Behavior The personality of educators in Islamic boarding schools, which tend to vary between extrovert and introvert, plays an important role in determining their leadership style and interactions with students and colleagues. Overall, developing the personality and professional behavior of educators must be a priority to create a conducive educational environment, improve the quality of learning, and encourage the progress of students at the As-Sulthon Mersam – Batang Hari Islamic Boarding School.